Propaganda from the American Civil War - Springer, Paul J. (ABC-CLIO, 2019)
"Offering comprehensive coverage for those examining Civil War propaganda, this volume provides a broad analysis of efforts by both Union and Confederate sides to influence public opinion of America's deadliest conflict"--